STUDENTS’ MOTIVATION IN WRITING CLASS USING OF CANVA: STUDENTS’ PERCEPTION - Yulinda Utami; Dewi Suriyani Djamdjuri (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2021)
This study aims to investigate students’ perception of using canva in writing class. This study used a qualitative descriptive approach and the research adapted questionnaire and also an interview to collect the data with ten students’ at Senior High School Bingin Teluk. The results of this study indicate that the use of Canva in the writing class has a positive impact on the participants. The positive impact is that Canva can increase students' motivation in writing classes, Canva can improve students' abilities in writing classes and Canva can also help students in writing classes. not only the positive impact that students have, but also obstacles in using Canva such as students having to have more time to design programs using Canva, and Canva has a premium account that we should pay for and there are some pictures which will appear and be provided without watermark.